Alternative models of municipal housing company in Ukraine - SHCHERBYNA, Andrii; NIKOLAIEV , Vsevolod (Ways to Improve Construction Efficiency, 2025)
The article examines a set of alternatives in the structure and functions of municipal housing companies (MHCs) – social housing providers – which are planned to be established in Ukraine based on investments and grants from international financial organizations and donors. The need to rebuild a significant portion of damaged housing and construct new units for Internally Displaced Persons (IDPs) requires expanded approaches, as the total demand for affordable housing reaches 500 thousand units (up to 80 billion euros in investments), significantly exceeding the volume of the basic EC/EIB model (40 thousand units). The specifics of the Ukrainian context – the dominance of private ownership and the deformed condominium model – lead to difficulties in loss assessment, joint decision-making, and the absence of an effective mechanism for revolving reconstruction financing, which underlines the necessity of flexible alternative models. The methodological basis of the study was project analysis, which was used to formulate possible model alternatives and propose the most acceptable ones, providing for the diversification of social housing provision forms. Based on international documents and the specific conditions of Ukrainian cities, the possibilities of integrating the reconstruction of damaged buildings, the completion of unfinished objects, and the transformation of ownership in existing apartments of inefficient owners are demonstrated. Acceptable options in the model configuration include, in addition to new construction, rebuilt and majorly repaired buildings, as well as the use of existing private apartments for rent. A special alternative is the Housing Company (HC) model in the form of a LLC (JSC), established at the building level with the participation of former co-owners and the MHC as a municipal participant. This model allows external investment in exchange for a share of ownership, creating a mechanism of joint communal-private ownership of the integral real estate object. The MHC acts as an investor in reconstruction/repair, and the HC carries out state registration and organizes building management. Residents (former full owners) may become partial tenants, while the change of shares in favour of the MHC is possible in case of insufficient funds from co-owners for subsequent repairs, which essentially replaces state subsidies by exchanging necessary assistance for ownership shares. The model can be modified by waiving the self-sufficiency of the MHC. Housing stock management implies that strategic functions (Property Management, Assets Management) must remain with the MHC, while maintenance and operation functions (Building Management, Facility Management) can be transferred to private companies. The obtained results are considered in the context of housing management as assets of housing enterprises (companies) – both municipal and private in the form of business entities.